TEACHERS AND ENVIRONMENTAL EDUCATORS: COLLECTIVE CONSTRUCTION OF ENVIRONMENTAL LEARNING ACTIVITIES ON THE MIGRATION OF THE MONARCH BUTTERFLY IN MEXICO - Roberto Méndez-Arreola (Universidad Nacional del Nordeste, 2022)
This paper presents a learning experience with teachers and environmental educators in Mexico interested in creating learning activities on the monarch butterfly's migration and generating a space for collaboration and exchange to enrich their experiences and didactic repertoires. First, the document shows those aspects central to the design of the intervention based on an environmental learning approach through participation and involvement in collaborative design and production activities. These aspects aimed to build a project that contests more traditional and entrenched practices in environmental education based on visions of learning as an individual and school process. Second, the article shows the use of different digital tools to solve isolation derived from the pandemic caused by COVID-19, but above all, to facilitate and sustain collective work, as well as for writing, the exchange of information, and dialogue between participants. Third, the paper shows how those involved participated, the lessons learned, and a general description of the designed activities. Finally, some tensions and limitations that arose throughout the process are shown.